PENGARUH PREFERENSI RISIKO, KEWAJIBAN MORAL DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI KASUS PADA KANTOR SAMSAT CINERE KOTA DEPOK II) - Rifki, Muhamad (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze the influence of risk preferences, moral obligations, and tax socialization on taxpayer compliance. This study was conducted on motor vehicle taxpayers registered at the Cinere Samsat Office, Depok City II with a population of 390,126 taxpayers so that the number of samples was determined with the Slovin test at a margin of 10% of 100 taxpayers, with a sampling technique using Accidental Sampling. The data used in this study are primary data through the distribution of questionnaires. The data analysis technique in this study is multiple linear regression using SPSS 22 software. The results of the study indicate that risk preferences, moral obligations, and tax socialization simultaneously affect the compliance of motor vehicle taxpayers. Risk preferences do not affect the compliance of motor vehicle taxpayers. Moral obligations affect the compliance of motor vehicle taxpayers. Tax socialization does not affect the compliance of motor vehicle taxpayers. Based on the results of the study, it is expected that there will be an increase in motor vehicle taxpayer compliance through improvements and enhancements of risk preferences, moral obligations, and tax socialization.